Web-based Automatic Monitoring & Scheduling Management of Highland Plantation on Low Ground - Hasan, Zulhasnizam; Mazlan, Mumtazahiqa; Muhammad Mustafa, Ahmad Nizamuddin; Mohd Ali, Nursabillilah; Shibghatullah, Abdul Samad (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper proposes an automatic monitoring and scheduling management system for growing highland plants on the low ground. It is hypothesized that the plantation of highland plants on low ground is possible if the basic necessities such as temperature, humidity, lighting and water are monitored and controlled to suit their needs. Basically, this automatic system uses temperature, humidity and light sensor to detect the temperature readings, percentage of relative humidity and light availability respectively. The obtained values are sent to Raspbery Pi and are used for controlling the environment parameters. The desired conditions for the plantation are that the temperature must be below 20 degrees Celsius, the relative humidity must be higher than 60% and the lighting must be sufficient. In case any of the conditions is not achievable, mist spray, peltier and UV light will take respective action to stabilize the condition back to the desired setting. Interestingly, this system allows users to monitor environmental humidity and temperature as well as current activities at the plantation through the website in real time. The results show the system is functioning well since fragile highland plants such as strawberry could survive in normal indoor low ground condition for a fortnight.